Capacity Building and Retention of Human Resource: The Challenges and Opportunities in Nepalese Community Campuses - Bhattarai, Bimal (BARUN Journal, 2025)
Community campuses in Nepal face significant human resource challenges, particularly in recruitment, retention, and capacity building, due to limited financial resources and lack of professional development opportunities. Addressing these issues through HR innovations, such as digital tools and collaborative partnerships, is essential for enhancing institutional sustainability and employee well-being. This study aims to analyze the human resource challenges, policies, and innovative strategies for improving recruitment, capacity building, and staff retention in resource-constrained community campuses in Nepal. The study employs a qualitative review design, analyzing secondary data from peer-reviewed sources to explore recruitment, capacity building, and retention challenges in Nepalese community campuses using a thematic approach and ethical standards. This study is significant in improving human resource management in Nepalese community campuses by addressing capacity building, staff retention, and HR strategies, ultimately enhancing academic quality, equity, and inclusive. Key findings highlight the human resource challenges in Nepalese community campuses, including recruitment and retention issues, insufficient professional development, and ineffective HR policies, while suggesting innovative strategies like peer mentoring, online training, and partnerships to enhance capacity-building and staff retention. In conclusion, Nepalese community campuses can address HR challenges by adopting innovative, cost-effective strategies and aligning HR policies with faculty needs to foster professional growth and ensure long-term sustainability.